PHYSICS EDUCATION AT AN EVENING COURSE OF A JAPANESE UNIVERSITY - Umemura, Kazuo; Tomura, Akihiro (PEOPLE: International Journal of Social Sciences, 2018)
The evening undergraduate course of Tokyo University of Science (TUS) accepts 360 students every year. A predecessor school of this course was established in 1881, thus, the evening course has a 137-year history. Furthermore, this is the only evening school at the Faculty of Science in a Japanese university at present. Although the evening course has provided an opportunity for higher education in the natural sciences for citizens who graduated from high school, new demands for lifelong education in the evening course have now appeared. This paper statistically summarizes the present situation of science education in the evening course, and then discusses the future of the evening course.